2010
DOI: 10.1902/jop.2010.090688
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cytokine and Periodontal Profiles in Relation to Disease Activity of Rheumatoid Arthritis in Japanese Adults

Abstract: These results suggest that the disease activity of RA correlated with serum levels of IL-6, TNF-alpha, and CRP, and it might influence BOP in the patients with moderate to high disease activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
63
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 34 publications
5
63
1
2
Order By: Relevance
“…Regarding the role of TNF-α in RA and CP, studies have indicated a positive relationship between TNF-α and RA and CP. Similar to TNF-α levels, proinflammatory cytokine levels in GCF and serum tend to increase with periodontal inflammation (14) and decrease after periodontal treatment in both CP and RA patients (29,30). Moreover, in another study, anti-TNF-α therapy in RA patients lowered GCF TNF-α levels and caused milder periodontal disease compared with patients who had not received anti-TNF-α therapy (31).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Regarding the role of TNF-α in RA and CP, studies have indicated a positive relationship between TNF-α and RA and CP. Similar to TNF-α levels, proinflammatory cytokine levels in GCF and serum tend to increase with periodontal inflammation (14) and decrease after periodontal treatment in both CP and RA patients (29,30). Moreover, in another study, anti-TNF-α therapy in RA patients lowered GCF TNF-α levels and caused milder periodontal disease compared with patients who had not received anti-TNF-α therapy (31).…”
Section: Discussionmentioning
confidence: 91%
“…TNF-α plays a critical role in host response against a wide range of bacterial infections and contributes to both innate and adaptive immune responses in diseases such as CP and RA (14,28). Regarding the role of TNF-α in RA and CP, studies have indicated a positive relationship between TNF-α and RA and CP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in Sweden, Brazil, USA, Turkey, and Japan, however, did not find a higher prevalence and severity of periodontitis in RA patients [10][11][12][13][14] . In other words, the prevalence and severity of periodontitis in RA patients may be influenced by genetic, dietary, cultural and other differences associated with differences in nationality and ethnicity.…”
mentioning
confidence: 76%
“…Although various studies have assessed the association between periodontitis and RA [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] , no study has yet investigated the effect of using several definitions for periodontitis prevalence and severity on the association between periodontitis and RA.…”
mentioning
confidence: 99%